The Effect of the Guided Discovery Style according to the Scheduling of Sequential and Random Exercise on Learning some of the Motor Skills in Artistic Gymnastics for Female Students - Moaid, Ghada (Journal of Physical Education, 2014)
The study aimed to set an educational curriculum using the Guided Discovery Style according to the scheduling of sequential and random exercise and to identify the effect of the Guided Discovery Style according to the scheduling of sequential and random exercise on learning some of the motor skills in artistic gymnastics for female students. The researcher has assumed that there are statistically significant differences between pre and post tests for the groups of the study in learning some of the motor skills in artistic gymnastics for female students. The experimental method has been used in the study and the subjects were selected out of the fourth grade students in Dijlah Secondary School for girls. The subjects were divided into three groups; two were experimental and submitted to the Guided Discovery Style according to the scheduling of sequential and random exercise in learning motor skills. The control group, on the other hand, submitted to the Command-Style. After collecting and analyzing data, conclusions came out to prove that the Guided Discovery Style is effective in learning the skills in question. The results also showed the superiority of the first and the second experimental groups then the control group